Medical management of unruptured interstitial pregnancy with mifepristone and methotrexate - Karki, Usha; Saha, Rachana (Journal of Kathmandu Medical College, 2016)
Ectopic pregnancy is a serious complication of pregnancy in which embryo gets implanted any where other than the uterine cavity. In interstitial pregnancy, the pregnancy is located in that part of the fallopian tube that penetrates the muscular layer of the uterus. Overall incidence of ectopic pregnancy is one to two percent among which the incidence of interstitial pregnancy is only two percent. Interstitial pregnancy being the hazardous type requires immediate management. Though surgical treatment is the management of choice, its association with decreased fertility rate and increased rate of uterine rupture in future pregnancy cannot be ignored. We hereby report of medical management of interstitial ectopic pregnancy with single oral dose of Mifepristone 200mg along with single dose of Methotrexate 50miligram intramuscularly. Journal of Kathmandu Medical College, Vol. 4(1) 2015, 34-36